Particulate Matter Pollution: A Continuing Problem in Tirana’s Air Quality: Status and Trends - Totoni (Lilo), Raimonda; Prifti, Luela; F. Mulla, Edlira (Asian Journal of Chemistry, 2012)
Air quality monitoring in Tirana city in the last two decades has indicated that air pollution from particulate matter is the main problem of the urban air quality. This pollution is especially high near areas with a great traffic density, thus showing that road traffic remains the main source of air particulate matter emissions. The measurements carried out for 15 months (April 2008-June 2009) regarding the total suspended particulate (TSP) and particulate matter less than 10 microns (PM10) in one of the main cross-roads of Tirana city resulted in values that continuously exceed the national norms for these air pollutants. Comparison of results from this study with PM10 levels in a former study carried out in the period 1997-1998 in the same monitoring point evidences a reduction of PM10 concentrations by 70 μg/m3, which could be explained by improvements made in infrastructure and measures taken regarding the controlling of pollution sources.